Practices in assessing fatigue and performance over matches in combat sports: A brief review - Kons, R. L.; Saldanha da Silva Athayde, M.; Till, J. E.; Cloak, R.; Detanico, D. (Strength and Conditioning Journal, 2026)
Combat sport athletes frequently compete in multiple high-intensity matches within a single day, leading to progressive acute fatigue that compromises neuromuscular and physiological performance. This review aimed to describe the methodological approaches used to assess fatigue and performance during simulated and official combat sport competitions. Simulated match protocols, predominantly applied in grappling disciplines, such as judo, wrestling, and Brazilian jiu-jitsu, enable greater experimental control and facilitate comprehensive physiological and performance monitoring, including physiological markers (e.g., heart rate, blood lactate concentration, and cortisol) and strength and power performance. Conversely, assessments conducted during official competitions are limited by logistical constraints and typically rely on noninvasive or rapid measures, such as handgrip strength, jump tests, heart rate, and subjective ratings. The evidence indicates that simulated environments allow for a broader and more complex range of measurements, while official contexts provide higher ecological validity but reduced methodological control. A synthesis of the literature highlights the importance of selecting assessment strategies according to research goals and competitive context. These perspectives contribute to optimizing training monitoring and fatigue management strategies in combat sports, supporting the integration of reliable physiological and subjective indicators into both experimental and applied performance settings.